Retorika Komunikasi Aa Gym dalam Kajian Al-Hikam “Jangan Sia-Siakan Waktu” - Yousef Bani Ahmad (Indonesian Journal of Applied Linguistics Review, 2022)
The purpose of this study is to find out what the rhetorical element in Aa Gym's oral discourse looks like when delivering its da'wah message to the congregation regarding the study of Al-Hikam with the topic “don't waste time" and then how to use the rhetorical function of Aa Gym in conveying its da'wah message to the congregation. This research uses a qualitative-descriptive approach with content analysis. The data source is taken from a youtube video, the Media Da'wah Hikmah TV channel. The findings of the study conducted are that speakers have great persuasion in every sentence that is simple and easy to understand, conciliatory intonation and calm body language. In the content of the conversation, everything is assembled and conceptualized with a good plot. The opening, body and closing sentences are able to arouse the feelings of those who hear them. Judging from the audience, they are very happy and comfortable when listening to Aa Gym's lectures that are in accordance with the realities of life. The rhetorical function used by Aa Gym when delivering its da'wah is corrective, instructive and suggestive rhetorical functions. The expected implication in this research is knowledge of da'wah strategies that can be applied with a rhetorical approach to be able to convey sentences in oral discourse that are able to give influence and have a good impact on listeners.